만성폐쇄성폐질환 동물모델에서 SGX01의 폐손상 억제 효과 - 박재준; 양원경; 유이란; 김승형; 박양춘; Park, Jae-jun; Yang, Won-kyung; Lyu, Yee Ran; Kim, Seung-hyung; Park, Yang Chun (대한한방내과학회지, 2019)
Objective: This study aimed to evaluate the inhibitory effects of SGX01 on the lung injuries of COPD mice model. Materials and Methods: This study was carried out in two ways: in vitro and in vivo. In vitro, L929 cells were challenged with LPS, and then treated with six concentrations of SGX01 (10, 30, 50, 100, 300, and $500μg/ml$) and analyzed by ELISA. In vivo, C57BL/6 mice were challenged with LPS and cigarette smoking solution (CSS), and then treated with a vehicle only (control group), dexamethasone 3 mg/kg (dexa group), or a SGX01 200 mg/kg (SGX01 group). After sacrifice, the BALF or lung tissue was analyzed with Cytospin, FACS, ELISA, real-time PCR and H&E, and Masson's trichrome staining. Results: SGX01 significantly decreased NO, $TNF-α$, and IL-6 on L929 cells challenged with LPS. In the COPD model, SGX01 significantly inhibited the increase of neutrophils, $TNF-α$, IL-17A, CXCL-1, MIP2, CD8+ cells in BALF, and $TNF-α$, $IL-1β$ mRNA expression in lung tissue. It also decreased the severity of the histological lung injury. Conclusion: This study suggests the usability of SGX01 for COPD patients by controlling lung tissue injury.